Outcomes for Pressure Ulcer Trials (OUTPUTs) project: review and classification of outcomes reported in pressure ulcer prevention research. (27th July 2020) - Lechner, A.; Kottner, J.; Coleman, S.; Muir, D.; Beeckman, D.; Chaboyer, W.; Cuddigan, J.; Moore, Z.; Rutherford, C.; Schmitt, J.; Nixon, J.; Balzer, K.
Summary: In order to overcome inconsistencies in the reporting of outcomes in clinical trials, core outcome sets (COSs) have been developed in many clinical areas and the awareness of this concept is growing steadily. The Outcomes for Pressure Ulcer Trials (OUTPUTs) project aims to improve the quality of evidence from pressure ulcer prevention trials by developing a COS. As an initial step in the COS process we aimed to identify and classify both outcomes and concepts that represent potential outcomes for future trials that have been reported in pressure ulcer prevention research. A review was conducted in 12 major databases covering the literature indexed until 2016. Outcomes and relevant concepts reported in primary studies and/or reviews on pressure ulcer prevention in adult patients were extracted as presented in the articles, and afterwards inductively grouped into outcome domains. The domains were then categorized according to the outcome domain taxonomy recently proposed by the COMET group. In total 332 studies were included and 68 outcome domains were identified, covering multiple aspects of pressure ulcer prevention. Pressure ulcer occurrence was reported in 71% of all included studies, representing the most frequent outcome, followed by costs (22% of all studies) and acceptability of intervention and comfort (18% of all studies). A plethora of different outcomes are applied in pressure ulcer prevention research and substantial variations in definitions and reporting of similar outcomes were observed. A COS for pressure ulcer prevention trials is needed to overcome the noncomparability of outcomes. Abstract : Linked Comment:  Lechner. Br J Dermatol 2021; 184 :587 .